Edukasi Protokol Kesehatan 5M Terhadap Peningkatkan Pengetahuan, Sikap dan Perilaku Pencegahan Covid-19 Masyarakat Desa Grogolpenatus, Kecamatan Petanahan, Kabupaten Kebumen - Rifa Ulfah; Mahardhika Cipta Raharja (Da'wa Faculty IAIN Purwokerto, 2021)
Coronavirus disease 2019 (Covid-19) is an infectious disease that attacks the respiratory system and it was declared a pandemic in 2020. The Indonesian government has made the 5M health protocol as a prevention against the transmission Covid-19. However, there are some people (including residents of Grogolpenatus Village) who do not implement the health protocol. This quantitative study uses a pre-experimental design with a “one group pretest-post test” approach. The population in this study were residents of Grogolpenatus Village aged 31-59 years, 30 of them were randomly selected to be the sample. Data collection techniques of structured interviews used instruments in pre-test and post-test questionnaires. Data were analyzed using bivariate analysis Wilcoxon. The results showed that there was an effect of education on the 5M health protocol on knowledge (p=0.00), attitudes (p=0.00), and Covid-19 prevention behavior (p=0.00) in residents of Grogol Penatus Village, Petanahan District, Kebumen Regency